Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1177/104063871002200418
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ptfA Gene of Avian Pasteurella Multocida Strains by Allele-Specific Polymerase Chain Reaction

Abstract: Abstract. Pasteurella multocida is the causative agent of fowl cholera in domesticated and wild birds. The disease outcome is affected by various host-and pathogen-specific determinants. Several putative virulence factors have been proposed to play a key role in this interaction, including the ptfA gene, the products of which assemble to form type 4 fimbriae on the bacterial surface. One way to understand more precisely how ptfA contributes to pathogenesis is to gather molecular features of this gene in circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The Type IV fimbriae are formed by repeated subunits and present a highly conserved N-terminal nucleotide sequence (Hatfaludi et al 2010). In a recent study, Sellyei et al (2010) identified only two major alleles of ptfA among 31 strains of different sero- Doughty et al (2000), this gene is a candidate for heterologous vaccine development (Ewers et al 2006). The hemagglutinin PfhA was identified in 15/25 strains (60%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Type IV fimbriae are formed by repeated subunits and present a highly conserved N-terminal nucleotide sequence (Hatfaludi et al 2010). In a recent study, Sellyei et al (2010) identified only two major alleles of ptfA among 31 strains of different sero- Doughty et al (2000), this gene is a candidate for heterologous vaccine development (Ewers et al 2006). The hemagglutinin PfhA was identified in 15/25 strains (60%).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that among the adhesins identified in samples of P. multocida, including pfhA, tad, ptfA, fimA, and hsf-1,2, only the latter three are present in all pathogenic strains (Sellyei et al 2010). The ptfA gene, which encodes a subunit of type IV fimbriae, was found in 23/25 samples (92%), a result similar to that observed in other studies (Ewers et al 2006, Bethe et al 2009, Tang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted using a commercial kit c as described previously. 12 The 16S rDNA (1235 nucleotide in length) was amplified by PCR carried out in a 50-μl volume that was comprised of 5 μl of DNA template, 12.5 pmol of each modified universal primer d (forward: 5′-AGAGTTTGATCATGGCTCAG-3′, position 9-29; reverse: 5′-CCATTGTAGGACGTGTGAAGCCC-3′, position 1222-1244) in 1× PCR buffer, e 200 nM deoxyribonucleotide triphosphate mix, e and 1.25 U commercial DNA polymerase.…”
mentioning
confidence: 99%
“…Genes were detected by PCR as previously described (Tang et al, 2009;Sellyei et al, 2010). All reactions were performed using a C1000 Thermal Cycler (BioRad Laboratories, Inc., Berkeley, CA, USA).…”
Section: Virulence-associated Genesmentioning
confidence: 99%